(untitled) (Tempo e Argumento, 2019)
This paper investigates possible connections between History and the Internet. The starting point of this discussion is an acknowledgement of the presence of the Internet in social life, and its impact in the ways of obtaining and publicizing knowledge. More specifically, a discussion will be presented on how the Internet has been producing new documents for the work of historians and, better yet, how they have dealt with such sources. In order to do so, a few studies performed by historians are listed as utilizing the Internet as source. In this section, the idea is to point out what digital documents have been chosen by historians to perform their analyses, what difficulties they face, and what potential these sources have. It is understood that the Internet has great potential for historiographic work and, notably, for Present-Day History. The second part of this paper presents information on the research on Brazilian websites whose theme is historical landmarks, with the objective of investigating narratives produced and presented in school-level research websites about Brazilian historical landmarks. At this stage, the discussion is focused on debating the uses of History performed by these spaces. It is noticeable that they present narratives in which historical facts are presented linearly and in a simplified manner, following the so-called Traditional History. This two-way observation is expected to contribute with the debate on this important matter of the production and divulging of historical knowledge. Keywords: History – Teaching and Learning, The Internet.